a - Muhammad Alfreda Daib Insan Labib; Dwi Langgeng Jauhari (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2023)
This article aims to explain Bulughul Maram's book and its lecturers' characteristics, namely the book Subulussalam and Misbahus Dzalam. Kitab Bulughul Maram is a phenomenal book among Indonesian students, especially for modern-based cottage students. Many scholars have given lectures to this book both from foreign scholars and even Indonesian scholars. The method used in this paper is a qualitative approach with library research which is a descriptive analysis of literature studies to enrich this study as the main source. As for the results of this research, Kitab Bulughul Maram plays an important role in Islamic civilization, especially in Indonesia. Its phenomenality is reflected in the high interest from various circles with various ideologies. This book is proof that religious science has universal appeal, transcending geographical and ideological boundaries. It can be seen from various indicators and enthusiasm for Bulughul Maram through digital platforms, teaching, and discussions around this book at home and abroad.